Prolonged release of risperidone via gastro retentive drug delivery device - Kwan, Audrey Kai Xin (Nanyang Technological University, 2023)
The treatment goal for patients diagnosed with mental health conditions is to alleviate the symptoms to improve their psychosocial functioning. However, clinical studies revealed that approximately 50% of patients diagnosed with mental health problems are non-adherent to their treatment plan. Studies have also shown that psychopathology and psychosocial functioning worsen with repeated psychotic and mood episodes in schizophrenia and bipolar disorders. Therefore, relapse prevention is vital for the treatment of mental health disorders. This study proposes a floating gastric resident oral formulation that can deliver risperidone in the stomach over a prolonged period. The microparticles were fabricated using a solvent evaporation technique and the gastro-retentive device was fabricated using a mould casting technique. The polymeric microparticles made of PLGA and a polymeric blend of PLGA:PLLA (1:1) achieved 100% release of risperidone in-vitro within 21 days and 11 days respectively. Two variations of the device were fabricated: receptacle cup-and-lid (microparticles are encased within the device), and the matrix (microparticles are embedded in the hydrogel). Due to the fabrication flaws of the device, the influence of the device on the release profile of risperidone could not be determined accurately. However, the device displayed excellent floating capability as it floated in simulated gastric conditions for up to 21 days. This result established the functionality of this gastro-retentive oral for the extended release of risperidone in-vitro. Based on the mathematical modelling, PLGA free particles release data fit well with the Higuchi model for the first three days (r2 = 0.99144), and subsequent release follows first-order kinetics until day 21 (r2= 0.96517). For PLGA:PLLA (1:1) free particles, it fits well in the Higuchi model in the first three days (r2 = 0.9944), and subsequent release follows the Hixson-Crowell model (r2= 0.9668). This study established the potential to develop a floating oral formulation for prolonged gastro delivery to reduce dosing frequency and improve patient compliance. Future work can optimize the microparticles' yield and encapsulation efficiency, investigate the effect of polymeric formulations on release using uniform-sized microparticles. Improvements can be made for the device fabrication to minimize microparticle wastage and defects in the receptacle cup-and-lid design.